PENGARUH PEMBANGUNAN KEBUDAYAAN TERHADAP PEMBANGUNAN MANUSIA DI INDONESIA - Isna Zuriatina (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2020)
The diversity of Indonesian culture is a strong basic capital in development. The government has realized that cultural treasures in Indonesia are valuable assets. Cultural development is one of the government's efforts to improve the welfare and quality of human life in Indonesia. To measure the quality of human life, the Human Development Index (HDI) indicator is used, which explains how the population can access the results of development in obtaining income, health, education, and so on. The Cultural Development Index (CDI) is an instrument used to measure the achievements of cultural development performance, which consists of 7 dimensions, namely dimensions of cultural economy, education, socio-cultural resilience, cultural heritage, cultural expression, cultural literacy, and gender. To find out how much influence the CDI has on HDI in Indonesia, a simple linear regression statistical method is used. The result of this study illustrate that the CDI and HDI have a positive relationship, that is, the higher the CDI achievement, the higher the HDI achievement of a region. From the result of R Square shows that 40 percent of the HDI variable can be explained by the CDI variable, while the rest can be explained by other factors. Through a simple linear regression statistical analysis test found that every one percent increase in the CDI, will increase the HDI by 0.437 percent. This finding is expected to provide recommendations to the government regarding cultural-based national development. All development planning must also consider cultural development.